2003
DOI: 10.3171/spi.2003.98.2.0156
|View full text |Cite
|
Sign up to set email alerts
|

Results of preoperative embolization for metastatic spinal neoplasms

Abstract: Object. Arterial embolization reduces blood loss in patients undergoing surgery for hypervascular spinal tumors. The objectives of this study were twofold: 1) to evaluate the role of magnetic resonance (MR) imaging in predicting tumor vascularity and 2) to assess the effectiveness of preoperative embolization in devascularizing these tumors. Methods. Fifty-one patients with metasta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
3
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(68 citation statements)
references
References 23 publications
4
58
3
3
Order By: Relevance
“…Most of our patients had their surgery for metastases in thoracic spine (21), and it is not really possible to compare this with the small number at other sites-cervical (2) and lumbar (2). However, Prabhu et al [13], in their series of 51 patients, found thoracic (2,300 ml) and lumbosacral tumours (3,700 ml) to be associated with significantly more blood loss than those of the cervical region (1,500 ml; p = 0.015).…”
Section: Discussionmentioning
confidence: 83%
See 4 more Smart Citations
“…Most of our patients had their surgery for metastases in thoracic spine (21), and it is not really possible to compare this with the small number at other sites-cervical (2) and lumbar (2). However, Prabhu et al [13], in their series of 51 patients, found thoracic (2,300 ml) and lumbosacral tumours (3,700 ml) to be associated with significantly more blood loss than those of the cervical region (1,500 ml; p = 0.015).…”
Section: Discussionmentioning
confidence: 83%
“…Of the 19 patients with neurological deficit, 13 had a progressive neurological deficit and were operated on at a mean of 26 (1-60 days) from the onset of symptoms. Neurological status at presentation, evaluated on the basis of Frankel grade was Frankel C (6), Frankel D (13) and Frankel E (6). The mean estimated blood loss in all patients was 1,696 (400-5,000) ml; mean operating time was 276 (90-690) min and an average of 2.3 (0-7) units of whole blood was transfused.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations